Similar temperature dependencies of glycolytic enzymes: An evolutionary adaptation to temperature dynamics? - Cruz, Ana Luisa B.; Hebly, Marit; Duong, Giang-Huong; Pronk, Jack T.; Heijnen, Joseph J.; Daran-Lapujade, Pascale; Van Gulik, Walter M.; Wahl, Sebastian Aljoscha (BMC Systems Biology, 2012)
Background: Temperature strongly affects microbial growth, and many microorganisms have to deal with temperature fluctuations in their natural environment. To understand regulation strategies that underlie microbial temperature responses and adaptation, we studied glycolytic pathway kinetics in Saccharomyces cerevisiae during temperature changes.Results: Saccharomyces cerevisiae was grown under different temperature regimes and glucose availability conditions. These included glucose-excess batch cultures at different temperatures and glucose-limited chemostat cultures, subjected to fast linear temperature shifts and circadian sinoidal temperature cycles. An observed temperature-independent relation between intracellular levels of glycolytic metabolites and residual glucose concentration for all experimental conditions revealed that it is the substrate availability rather than temperature that determines intracellular metabolite profiles. This observation corresponded with predictions generated in silico with a kinetic model of yeast glycolysis, when the catalytic capacities of all glycolytic enzymes were set to share the same normalized temperature dependency.Conclusions: From an evolutionary perspective, such similar temperature dependencies allow cells to adapt more rapidly to temperature changes, because they result in minimal perturbations of intracellular metabolite levels, thus circumventing the need for extensive modification of enzyme levels. © 2012 Cruz et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2022-01-11
Keywords: Glycolysis; Kinetic modelling; Metabolomics; Saccharomyces cerevisiae; Temperature dynamics